Pendekatan Konseptual dalam Manajemen Institusi Pendidikan Islam: Prinsip, Karakteristik, dan Implementasi - Sofiatus Sobriyah; Fajar Ainol Yakin (Politeknik Kampar, 2024)
This research aims to analyze the basic concept of management of Islamic educational institutions, which is a strategic aspect in improving the quality of education based on Islamic values. This research uses a descriptive-qualitative approach with a literature review method of primary and secondary sources. The results showed that the management of Islamic educational institutions has distinctive characteristics that distinguish it from educational management in general, namely based on theological, rational, empirical, and theoretical values. Its main characteristics include a theoanthropocentric orientation, the implementation of an emancipatory mission, and the transformation of mindsets towards effectiveness and efficiency in line with Islamic teachings. In addition, this management also plays an important role in supporting the integration of education based on spiritual and moral values in a modern context. This research provides practical implications for the management of Islamic educational institutions to be more adaptive to global challenges without losing their Islamic identity